Psychological aspects of inclusive setting for children with disabilities - Scherbakova, Anna (Social Welfare: Interdisciplinary Approach, 2015)
The article discusses the issues of inclusive approach. The approach is assumed to aim at ensuring self-fulfilment of every community member. Regarding children with disabilities, the notion of inclusive setting means the setting for rehabilitation, providing them with activities and maintaining their independent living. The major obstacle is inconsistence and indistinctiveness of how people understand any possible models of living of people with disabilities. The ambivalence is reasoned mostly by the difference of personal attitudes, and feelings and emotions of population towards people with disabilities. The article points out a sharp difference of the attitude towards a disabled person as a generalized notion and a mentally retarded person.
Keywords: inclusive setting; rehabilitation; rehabilitative environment; special needs; disability; mental retardation